A Study of Management Corporation Financial in High Rise Residential with Correlation of Management Fund and Facilities Provided - Nurakmal, Abdullah@ Goh Tuo Ho; Norngainy, Mohd Tawil; Yuzainee, Md Yusoff; Che-Ani, A. I.; Surat, M. (Elsevier B.V., 2012)
Housing plays an important role in property finance for national economic point of view. It is a long term investment which becomes source of income for many parties. In recent years, most of urban areas in Malaysia are looking forward to live in stratified unit compared to other types of housing. Limitation of land availability and increasing of property value have contributes to more construction and development on high rise residential. This residential type is more economical compared to landed property. In the other hand, each complex of high residential building needs a body to manage all shared-property such as facilities, road and pathway, lighting and so on which namely Management Corporation (MC). Many researches have been conducted to determine the problems faced by MC in managing highrise residential matters. The most common problem faced by MC is poor collection of maintenance fund. Thus, it was effecting the management financial. The tenant refuses to pay the maintenance fund due to dissatisfaction of work done by MC. Briefly, this study explained the determination of actual amount of maintenance fund to be applied to high rise tenants according to facilities provided. The study employed questionnaires to obtain information from fifty tenants of different residential areas around Klang valley, Malaysia. From the questionnaires, a few data were collected such as strata type, price of house unit, price of maintenance fee and type of facilities provided. The result of this research, it found that determination of maintenance fund price was subjected to facilities provided in the residential area.